Cytotoxicity and anti-inflammatory activity of ethanol extract of Artocarpus altilis (Parkinson ex F.A.Zorn) Fosberg leaf in lipopolysaccharide-stimulated RAW 264.7 cells - Fitrya; Muharni; Fatma Sri Wahyuni; Annisa Amriani (Journal of Pharmacy & Pharmacognosy Research, 2023)
Context: The flavonoid and phenolic compounds found in Artocarpus altilis have made their popularity. This plant has been used as a traditional medicine in Indonesia for various diseases.